Survival trends of extracorporeal membrane oxygenation support for pediatric emergency patients in regional and metropolitan areas in Japan - Noriyuki Kaku; Wakato Matsuoka; Kentaro Ide; Takaaki Totoki; Katsuki Hirai; Soichi Mizuguchi; Kanako Higashi; Kenichi Tetsuhara; Hazumu Nagata; Satoshi Nakagawa; Yasuyuki Kakihana; Akira Shiose; et al. (Pediatrics and Neonatology)
Background: To assess the performance of pediatric extracorporeal membrane oxygenation (ECMO) centers, outcomes were compared between metropolitan and other areas. Methods: A retrospective cohort study was conducted at three regional centers on Kyushu Island and the largest center in the Tokyo metropolitan area of Japan. The clinical outcomes of patients of ≤15 years of age who received ECMO during 2010–2019 were investigated, targeting the survival and performance at discharge from intensive care units (ICUs), using medical charts. Results: One hundred and fifty-five patients were analyzed (regional, n = 70; metropolitan, n = 85). Survival rates at ICU discharge were similar between the two areas (64%). In regional centers, deterioration of Pediatric Cerebral Performance Category (PCPC) scores were more frequent (65.7% vs. 49.4%; p = 0.042), but survival rates and ΔPCPC scores (PCPC at ICU discharge–PCPC before admission) improved in the second half of the study period (p = 0.005 and p = 0.046, respectively). Veno-arterial ECMO (odds ratio [OR], 3.00; p < 0.03), extracorporeal cardiopulmonary resuscitation (OR, 8.98; p < 0.01), and absence of myocarditis (OR, 5.47; p < 0.01) were independent risk factors for deterioration of the PCPC score. A sub-analysis of patients with acute myocarditis (n = 51), the main indicator for ECMO, revealed a significantly higher proportion of cases with deteriorated PCPC scores in regional centers (51.9% vs. 25.0%; p = 0.049). Conclusions: The survival rates of pediatric patients supported by ECMO in regional centers were similar to those in a metropolitan center. However, neurological outcomes must be improved, particularly in patients with acute myocarditis.